2022
DOI: 10.1186/s12889-022-13690-z
|View full text |Cite
|
Sign up to set email alerts
|

Health-promoting factors among students in higher education within health care and social work: a cross-sectional analysis of baseline data in a multicentre longitudinal study

Abstract: Background Educational environments are considered important in strengthening students’ health status and knowledge, which are associated with good educational outcomes. It has been suggested to establish healthy universities based on a salutogenic approach – namely, health promotion. The aim of this study was to describe health-promoting resources and factors among first-semester students in higher education in healthcare and social work. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…In another study, it was also stated that the average score of behavior in health promotion in female participants increased after 3 months of intervention [39]. These findings are also consistent with the results of studies that found health promotion interventions lead to increased attitudes toward health-related behaviors, improved skills, and healthy living behaviors [2], [40].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In another study, it was also stated that the average score of behavior in health promotion in female participants increased after 3 months of intervention [39]. These findings are also consistent with the results of studies that found health promotion interventions lead to increased attitudes toward health-related behaviors, improved skills, and healthy living behaviors [2], [40].…”
Section: Discussionsupporting
confidence: 79%
“…Health issues have long been a concern among higher education institutions, including health promotion among the campus community. This health promotion-based approach can potentially increase the university's contribution to improving the health of its population [2]. Universities can do many things to promote and protect the health of students and the entire academic community [3].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work mentioned that integrating student participation in school education and health promotion is of great importance during education and in preparing for future work and professional roles of health professionals. [ 37 ]…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with the advancement of technology and the widespread dissemination of health education ( 12 14 ), an increasing number of college students have begun to spontaneously engage in fitness activities, including working out alone, participating in group sports, and using fitness applications ( 5 , 15 , 16 ). From the perspective of agency, the stages of a person's fitness behavior can be divided into four phases: the transition from passive to active, then to autonomous, and finally to automatic (passive-active-autonomous-automatic) ( 17 ).…”
Section: Introductionmentioning
confidence: 99%